2005
DOI: 10.1080/03610730590882819
|View full text |Cite
|
Sign up to set email alerts
|

Music Enhances Category Fluency In Healthy Older Adults And Alzheimer's Disease Patients

Abstract: Exposure to some music, in particular classical music, has been reported to produce transient increases in cognitive performance. The authors investigated the effect of listening to an excerpt of Vivaldi's Four Seasons on category fluency in healthy older adult controls and Alzheimer's disease patients. In a counterbalanced repeated-measure design, participants completed two, 1-min category fluency tasks whilst listening to an excerpt of Vivaldi and two, 1-min category fluency tasks without music. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 13 publications
10
96
1
6
Order By: Relevance
“…Relaxing background music is therefore able to reduce anxiety levels and thus encourage autobiographical memory recall. These results confirm the findings observed by Thompson et al [27] on verbal fluency in the same type of population.…”
Section: Discussionsupporting
confidence: 83%
“…Relaxing background music is therefore able to reduce anxiety levels and thus encourage autobiographical memory recall. These results confirm the findings observed by Thompson et al [27] on verbal fluency in the same type of population.…”
Section: Discussionsupporting
confidence: 83%
“…Smith-Marchese (1994) reported an amelioration of cognitive deficits in AD patients that participated for six weeks in musical events, which comprised playing simple musical instruments, singing, and body movement. Thompson et al (2005) reported that exposure to classical music increased cognitive performance in AD patients, leading to better performances on category fluency tasks. Aldridge (1995) underlined that music therapy can enhance socialization and communication skills, leading to a greater cognitive stimulation of the patient.…”
Section: General Enhancement Of Cognitive and Social Functioningmentioning
confidence: 99%
“…A substantial body of structural and functional neuroimaging work in the healthy brain and in patients with focal brain lesions has delineated distributed cortico-subcortical networks that analyze the dimensions of music [6,12,13]: these networks closely overlap the networks targeted in canonical dementia syndromes [14,15]. However, to date most studies of music in dementia have focused on the interaction of music and memory [16][17][18], preserved abilities in trained musicians developing dementia [16,19,20] and potential benefits of music more widely in dementia [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%